Kandungan Logam Timbal, Besi, dan Tembaga dalam Air Minum Isi Ulang di Kota Bandung - Tih, Fen; Kusumawardani, Indah; Estevania, Margaret Yosephine; Simanjuntak, Ezra Artur Stefano (Zenit, 2015)
Water necessity is mostly fulfilled from drinking water, which should be in adequate quantity and quality. One of the sources of drinking water is refilled drinking water depots. As stated in health department rules (Permenkes RI Nomor 492/Menkes/Per/IV/2010), heavy metal content in drinking water cannot exceed the permitted level, including lead, iron and copper. The aim of this research is to determine whether there is over permitted level of lead, iron and copper content in refilled drinking water from depots throughout Bandung. This research is a descriptive survey with a cross sectional design. Thirty depots have been randomly selected from 150 registered depots in Bandung. Heavy metal contents are analyzed quantitatively with spectrophotometric method. The result shows that 30 samples do not have lead, iron and copper level content above the permitted level. However, some samples show almost a maximal level of heavy metal content which could influence health when consumed in the long termKeywords: refilled drinking water, lead, iron, copper